Factors Influencing Physical Activity in Cancer Patients During Oncological Treatments: A Qualitative Study. (December 2020) - Avancini, Alice; Tregnago, Daniela; Rigatti, Laura; Sartori, Giulia; Yang, Lin; Trestini, Ilaria; Bonaiuto, Clelia; Milella, Michele; Pilotto, Sara; Lanza, Massimo
Introduction: Although the literature supports the importance of physical activity in the oncological context, in Italy a large number of patients are not sufficiently active. Methods: The present study aimed to explore factors influencing an active lifestyle in cancer patients during oncological treatments. Semi-structured focus groups, including 18 patients with different cancer types, were conducted at the Oncology Unit in the University Hospital Trust of Verona (Italy). The interviews were audio-recorded, transcribed verbatim, and analyzed with content analysis. Results: According to the Health Belief Model, transcripts were categorized into the following themes: benefits, barriers, and cues to action. Patients reported a series of physical, physiological, and psychological benefits deriving from an active lifestyle. The main barriers hampering the physical activity participation were represented by treatment-related side effects, advanced disease, and some medical procedures, for example, ileostomy. Several strategies that can trigger patients to exercise were identified. Medical advice, social support from family and friends, features such as enjoyment, setting goals, and owning an animal can motivate patients to perform physical activity. At the same time, an individualized program based on patients' characteristics, an available physical activity specialist to consult, more detailed information regarding physical activity in the oncological setting, and having accessible structures were found important facilitators to implementing active behavior. Conclusions: Overall, patients have a positive view regarding physical activity, and a variety of obstacles and cues to action were recognized. Considering this information may help to improve adherence to a physical activity program over time, consequently increasing the expected benefits.